HUBUNGAN DAYA TARIK DAN POLA MENONTON PADA PROGRAM X-FACTOR RCTI TERHADAP KEPUASAN MENONTON - Jaka Atmaja (Universitas Bina Sarana Informatika, 2017)
One reality show program that attracts attention is the reality show X-Factor Indonesia. Impressions has a value of information and entertainment and educative get enough servings presented by television stations in Indonesia. Of phenomena that arise from the television, there is a change to the Patterns Watching the audience watching the show program .. business broadcasting station is required to have the widest possible creativity to produce a variety of interesting programs. This study aims to measure and describe how big the